Development of Phosphatidylcholine/Tween 80 based biocompatible clove oil-in-water nanoemulsion as a green nanocarrier for controlled herbicide delivery. (15th January 2022) - Kumar, Amit; Kanwar, Rohini; Mehta, Surinder K.
Abstract: Recently, the development of ecofriendly and biocompatible agrochemical delivery systems has garnered widespread attention because of their great potential in sustainable agri-food applications. Atrazine (ATZ) is a globally used herbicide used to control weeds, but it suffers from poor aqueous solubility, poor efficacy, and environmental loss. Herein, we report a novel, eco-friendly and biocompatible clove oil-based nanoemulsion as a green nanocarrier to enhance the solubility, bioavailability, and control release of ATZ. Food grade surfactants, Tween 80 and Phosphatidylcholine (PC) were used to formulate clove oil nanoemulsion with size <200 nm using ultrasonic emulsification technique, without any use of organic solvent. The ATZ encapsulation efficiency in NEm was greater than 95%. DLS confirms the nanosize (106 nm) and monodispersity of NEm. HRTEM reveals the spherical morphology of the nanodroplets. FTIR and DSC confirm the successful incorporation of ATZ inside the NEm oil droplet core. ATZ loaded NEm showed excellent thermal and storage stability, low Ostwald ripening rate, slow and sustained herbicide release behavior, which is of vital importance for an herbicide formulation. The release rate was better than commercial ATZ and free ATZ formulations. Results from herbicidal activity assays demonstrate that ATZ NEm exhibited excellent herbicidal activity even at low concentrations as compared to commercial ATZ analogs. In consideration of biocompatible excipients, free of organic solvent, and a simple fabrication process, ATZ loaded clove oil NEm can hold great potential in weed control and sustainable agri-food applications.